2023
DOI: 10.1037/ccp0000837
|View full text |Cite
|
Sign up to set email alerts
|

Within-patient association between emotion regulation and outcome in prolonged exposure for posttraumatic stress disorder.

Alice E. Coyne,
Elsa Mattson,
Jenna M. Bagley
et al.

Abstract: Objective: Difficulties with emotion regulation (ER) are a risk factor for the development and maintenance of posttraumatic stress disorder (PTSD). Less is known about temporal relations between ER and PTSD symptom change during treatment, including whether ER may represent a more potent change ingredient for some patients relative to others. This study examined the association between within-patient changes in ER and next-session PTSD symptom change and whether this association was more pronounced for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
0
1
Order By: Relevance
“…Our results align with Gilman and colleagues (2012), who found that improvements in hope—the opposite of despondence—during trauma‐focused cognitive therapy were a better predictor of subsequent reductions in PTSD symptoms than vice versa, providing initial evidence for the temporal precedence of change among these variables. Conversely, our results run counter to Coyne et al.’s (2023), who evaluated the temporal relations among emotion regulation—the opposite of affective dysregulation—and PTSD symptoms during an exposure‐based trauma‐focused treatment. The researchers observed that reductions in PTSD symptoms were a better predictor of subsequent improvements in emotion regulation than the reverse association.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results align with Gilman and colleagues (2012), who found that improvements in hope—the opposite of despondence—during trauma‐focused cognitive therapy were a better predictor of subsequent reductions in PTSD symptoms than vice versa, providing initial evidence for the temporal precedence of change among these variables. Conversely, our results run counter to Coyne et al.’s (2023), who evaluated the temporal relations among emotion regulation—the opposite of affective dysregulation—and PTSD symptoms during an exposure‐based trauma‐focused treatment. The researchers observed that reductions in PTSD symptoms were a better predictor of subsequent improvements in emotion regulation than the reverse association.…”
Section: Discussioncontrasting
confidence: 99%